All-Inorganic Perovskite Solar Cells With Both High Open-Circuit Voltage and Stability - Zhang, Lei; Hu, Tianle; Li, Jinglei; Zhang, Lin; Li, Hongtao; Lu, Zhilun; Wang, Ge (Frontiers in Materials, 2020)
Metal halide perovskite solar cells based on all-inorganic CsPbBr3 have attracted considerable attention recently, due to their high open-circuit voltage with good stability. However, the fabrication of CsPbBr3 film is limited by the poor solubility of cesium precursors in organic solvents by the one-step method. Here, we successfully fabricated CsPbBr3 film solar cells by employing colloid nanocrystal. The effects of technique parameters, including purification times, anneal temperatures, and spin-coating times on film morphology, optical spectra, and device performance are investigated in detail. The highest open-circuit voltage of 1.45 V and power conversion efficiency of 4.57% is achieved, which is mainly attributed to the high conductivity induced by the removal of organic ligands with increased nanocrystal electronic coupling. Furthermore, excellent stability in air is disclosed on the unencapsulated device suggesting the enormous potential for developing high open-circuit photovoltaic devices with high stability in future.